2010
DOI: 10.1007/s11547-010-0508-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the biliary and pancreatic system with 2D SSFSE, breathhold 3D FRFSE and respiratory-triggered 3D FRFSE sequences

Abstract: Three-dimensional FRFSE offers a significant benefit over conventional 2D imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In the present study, 3D MRCP exhibited the same capability for the visualization of the segment of pancreatic main duct as 2D MRCP, which is in agreement with the results of the study by Kim et al (12), Palmucci et al (3) and Sodickson et al (4), but other studies have reported varying results (2,5,18). The reasons for this may include that the pancreatic duct is sensitive to respiration (17) and that 2D MRCP exhibits superior in-plane resolution (4).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, 3D MRCP exhibited the same capability for the visualization of the segment of pancreatic main duct as 2D MRCP, which is in agreement with the results of the study by Kim et al (12), Palmucci et al (3) and Sodickson et al (4), but other studies have reported varying results (2,5,18). The reasons for this may include that the pancreatic duct is sensitive to respiration (17) and that 2D MRCP exhibits superior in-plane resolution (4).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 46 patients shows the typical features of CT and 42 patients shows the typical features of MRI were: (1) the dynamic nature of the enhanced feature of progressive nature of concentric enhancement, internal lesions was flaky, grid-like or liear strengthing; (2) intrahepatic duct dilatation; (3) capsular retraction; (4) satellite nodule is also seen. With the recent advances of imaging techniques, 3D MR cholangiopancreatography (3D-MRCP) is emerging as a promising technique due to its high image quality and ability to clarify anatomic relationships (Sodickson et al 2006;Glockner et al, 2007;Choi et al, 2008;Palmucci et al, 2010). The diagnostic procedures of IHHCC can be summarized as follows: clinical features 4 B-ultrasound 4 CT or MRI 4 surgical resection (radical resection or palliative resection or abdominal exploration) or stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…NonCartesian filling of k-space improves image quality, and imaging at 3T benefits in specific absorption rate reduction from variable flip angle refocusing techniques. 78,79 …”
Section: Magnetic Resonance Cholangiopancreatographymentioning
confidence: 99%